THE IMPORTANCE OF MECHANISMS FOR DEALING WITH THE CRISIS OF ENTERPRISES - Umarjon Mukhammadov (European Science Publishing, 2024)
In an era of economic volatility and rapid market changes, enterprises are increasingly susceptible to crises that can threaten their stability and long-term viability. This article explores the critical importance of implementing effective mechanisms for dealing with enterprise crises. It examines the various types of crises that organizations may encounter, including financial distress, operational disruptions, and reputational damage, and highlights the strategic approaches necessary for mitigating these risks. By analyzing case studies and best practices, the article provides insights into proactive crisis management techniques, such as robust risk assessment frameworks, contingency planning, and stakeholder communication strategies. Furthermore, it discusses the role of leadership and organizational culture in fostering resilience and adaptability. The article aims to underscore the necessity for enterprises to develop and maintain comprehensive crisis management plans, ensuring they are well-prepared to navigate and overcome challenges, thereby securing their long-term success and sustainability.
Keywords: Crisis, mechanisms, economic equilibrium, managers, competitiveness, bankruptcy, risk.